2015
DOI: 10.1007/s00603-015-0756-4
|View full text |Cite
|
Sign up to set email alerts
|

Review of Ground Characterization by Using Instrumented Drills for Underground Mining and Construction

Abstract: In underground mining, many miners are injured or lose their lives because of roof/pillar instability each year, and this is a persistent safety risk. Characterization of overlying strata is important for the design of safe and cost-effective ground support systems. Entry roof characterization can be performed by geological backmapping of the ground using various methods such as geophysical logging, borescoping, rock mass rating, and intelligent roof bolt drilling systems. This paper offers a brief review of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…In theory, various methods, including analytical, numerical, and experimental, can be used to analyze the applicability of MWD to the characterization of coalmine roofs [2][3][4][5][6][7][8]11,[15][16][17]. Analytical and numerical methods provide a straightforward means to understand the immediate effect of various geotechnical parameters on drilling and bolting operations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In theory, various methods, including analytical, numerical, and experimental, can be used to analyze the applicability of MWD to the characterization of coalmine roofs [2][3][4][5][6][7][8]11,[15][16][17]. Analytical and numerical methods provide a straightforward means to understand the immediate effect of various geotechnical parameters on drilling and bolting operations.…”
Section: Methodsmentioning
confidence: 99%
“…The literature has examples of laboratory experiments, field trials, and the development of instruments to monitor while drilling [2][3][4][5][6][7][8][9][10][11][12]. Reference [6] provided a brief review of recent improvements on instrumented drills used in ground characterization and highlighted issues that are still lagging in using these instruments. , Four instruments for roof bolt drills that can acquire roof data during roof drilling are discussed [6].…”
Section: Mwd Historymentioning
confidence: 99%
See 1 more Smart Citation
“…As emphasised by Scoble and Peck (1987), once ground characteristics are determined it would be possible to make real-time tactical decisions, such as blast design. Kahraman et al (2016) made a review of ground characterisation using instrumented drills for underground mining and construction. They indicated that MWD is used more in surface and shallow mining than in underground mining (Kahraman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With the technological advancements, recently more research in mining sector have been focused on MWD technique. Detailed information regarding rock type, lithology, rock strength (Hatherly et al 2015;Basarir and Karpuz 2016), ground characteristics (Kahraman et al 2015) can all be potentially determined from the recorded drilling parameters. This data recorded with respect to depth in the borehole must however be interpreted by direct comparison, correlation and calibration with core logs.…”
Section: Measurement While Drillingmentioning
confidence: 99%